“Menyama Braya”: Pondasi Utama Relasi Dialog Agama-Agama di Desa Dalung, Bali - Ferdinand Ludji; David Samiyono; Izak Y.M. Lattu (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
The purpose of this study is to describe and analyze the life values of the Balinese "Menyama Braya", as one of the values of "local wisdom" (local wisdom), which will be a common reference as social capital, and can sustainably become the main foundation or foundation in maintain harmony in inter-religious dialogue relations in the village of Dalung, Bali. Through the concept of life "braving", the social cohesion of the Dalung community so far has been maintained. This research uses a qualitative-descriptive approach. Primary data were obtained through in-depth interviews with: village government, religious leaders, and elements of community institutions as representatives of each religion. Finally, the results of the analysis of the data obtained show that "matching braya" can be used as the main foundation of inter-religious dialogue relations in the village of Dalung. By referring to the values of local wisdom which are the heritage of the ancestors as social capital, the Dalung people are able to offer patterns of inter-religious relations that promote relational dialogue and share humanist civilization values. This study aims to examine other social values, which are considered as supporting instruments of the concept of "equalizing braya", especially in building inter-religious dialogue relations to penetrate the boundaries of differences.